Teaching Trigonometry Based on Realistic Mathematics Education and Game-Based Learning Approach - Nguyen Tien Da; Do Diep Anh; Pham Thi Chau Giang; Phung Phuong Dung; Dang Bui Khanh Linh (Journal of Instructional Mathematics, 2024)
Trigonometry, often perceived as abstract and challenging, can hinder its potential to equip students with crucial mathematical skills. We propose a novel approach—"RME-GBL"—integrating Game-Based Learning (GBL) through engaging games with Realistic Mathematics Education (RME) for contextualized learning. This study investigates the combined impact of GBL and RME on 9th graders' understanding and problem-solving abilities in trigonometry. This study assesses the effectiveness of "RME-GBL" in enhancing conceptual understanding and problem-solving skills compared to traditional methods by employing a pre-test/post-test design with a control group. After the treatment applied in the experiment, the student learning group (N=30) with RME-GBL experienced an improvement in conceptual understanding and problem-solving skills, with their average scores significantly differing from the control group, indicating the effectiveness of the applied method or intervention. The results also showed that students in the RME-GBL group were more confident, more engaged, more motivated, and had a better conceptual understanding compared to traditional teaching methods. This research holds the potential to unlock new avenues for making trigonometry learning more captivating and effective for 9th graders.